Teachers' Attitudes towards Inclusive Education at Greek Secondary Education Schools - Maria Mouchritsa; Ainara Romero; Urtza Garay; Spyridon Kazanopoulos (MDPI AG, 2022)
Advocates of inclusive education believe in the right of all learners to education and the many benefits it delivers. Teachers' attitudes and beliefs toward inclusive education are instantly reflected in their classroom activities and practices. This research will concentrate on special and general education teachers in Greek secondary schools. It will investigate their attitudes toward inclusive education and how these attitudes alter as a consequence of variables such as age, gender, teaching experience, and inclusive education training. Quantitative, main, and correlational research was obtained between groups using a non-experimental technique. The sample was taken from 307 educators, who were almost equally divided between general and special education. The SACIE-R questionnaire was used to assess teachers' attitudes toward inclusive education. The outcomes of the research demonstrated that attitudes toward inclusive education were impacted by the kind of special education received, as well as age and general education teaching experience. Furthermore, positive attitudes were impacted by gender, but negative sentiments and concerns were influenced by general education and special education teaching experience. Finally, the study revealed low levels of negative sentiments, medium levels of concerns, and high levels of favourable attitudes toward inclusive education.